2004
DOI: 10.1063/1.1810216
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of ferromagnetic properties on carrier transfer at GaMnN∕GaN:Mg interface

Abstract: We report on the dependence of ferromagnetic properties of metalorganic chemical vapor deposition grown GaMnN films on carrier transfer across adjacent layers. We found that the magnetic properties of GaMnN, as a part of GaMnN∕GaN:Mg heterostructures, depend on the thickness of both the GaMnN film and the adjacent GaN:Mg layer and on the presence of a wide band gap barrier at this interface. These results are explained based on the occupancy of the Mn energy band and how the occupancy can be altered due to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…22 It has also been reported that the charge transfer occurs across adjacent layer in Ga 1−x Mn x N/ p-GaN : Mg and Ga 1−x Mn x N/n-GaN:Si heterostructures. 23 In that report, it has been indicated that a large number of electrons ͑holes͒ are transferred from adjacent n-type ͑p-type͒ layer into the sample. The difference thus may be explained by the scenario of the charge transfer from Sn-doped n-type GaN to Ga 1−x Mn x N ͑i.e., electron doping into Ga 1−x Mn x N͒.…”
Section: Methodsmentioning
confidence: 99%
“…22 It has also been reported that the charge transfer occurs across adjacent layer in Ga 1−x Mn x N/ p-GaN : Mg and Ga 1−x Mn x N/n-GaN:Si heterostructures. 23 In that report, it has been indicated that a large number of electrons ͑holes͒ are transferred from adjacent n-type ͑p-type͒ layer into the sample. The difference thus may be explained by the scenario of the charge transfer from Sn-doped n-type GaN to Ga 1−x Mn x N ͑i.e., electron doping into Ga 1−x Mn x N͒.…”
Section: Methodsmentioning
confidence: 99%
“…Reports of ͑Ga,Mn͒N epilayers synthesized in cubic and hexagonal crystal structures, of p-type and n-type ferromagnetic ͑Ga,Mn͒N, and of multiple ferromagnetic phases in one material all add to the complex phenomenology of these wide-gap DMSs ͑Korotov et al, 2001;Graf et al, 2002;Graf, Gjukic, et al, 2003;Arkun et al, 2004;Edmonds, Novikov, et al, 2005;Hwang et al, 2005;Sawicki, Dietl, et al, 2005͒. Uncertainties apply also to the interpretation of ferromagnetism seen in the ͑Ga,Mn͒P samples studied to date, which have been prepared by post-MBE ion implantation of Mn followed by rapid thermal ͑Theodor-opoulou et al., 2002;Poddar et al, 2005͒ or pulse-lasermelting annealing ͑Scarpulla et al, 2005͒. Experiments in these materials have not yet established unambiguously the nature of magnetic interactions in the ͑III, Mn͒P compounds.…”
Section: B Search For High Transition Temperaturesmentioning
confidence: 99%
“…The FM in GaMnN film could be due to RudermanKittel-Kasuya-Yosida (RKKY)/Zener indirect exchange interaction by itinerate holes (hole mediated) based on mean field approximation [3]. Doping with the shallow Mg acceptor has enhanced the FM of GaMnN films [7]. The exchange interaction between Mn ions and holes would result in ferromagnetic behavior of the GaMnN film.…”
Section: Introductionmentioning
confidence: 98%
“…The exchange interaction between Mn ions and holes would result in ferromagnetic behavior of the GaMnN film. To increase the hole concentration and hence saturation magnetization of the GaMnN film, various schemes have been used [7][8] 1.5 and 2.0 eV [8][9][10][11][12]. Deep acceptor bands result in insulating GaMnN films that makes difficult to realize GaMnN based ferromagnetic semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%